Regulating The Acquisition Of Inheritance Rights To Land For Children With Dual Nationality From Mixed Marriages Without A Marriage Agreement - Taradita Nindyawati; Rachmi Sulistyorini; Hanif Nur Widhiyanti (CV. AFDIFAL MAJU BERKAH, 2024)
Marriage is an important event in human life. A legal marriage means that the marriage complies with the law, religion and state. So all types of marriage are legal, as long as they follow the applicable rules, including mixed marriages. In general, mixed marriages make a pre-marital agreement with the purpose of avoiding the mixing of joint assets during the marriage period. Problems that often arise in mixed marriages are problems related to the nationality of children born from the marriage who have dual citizenship. This will certainly affect the determination of heirs regarding ownership of land and buildings in Indonesia. This research uses a normative juridical research method using two approach methods, namely the statutory approach and the conceptual approach. The research results show that the urgency of regulating the inheritance of land rights for children who have dual citizenship from the marriage of their parents is to provide legal certainty. Appropriate arrangements regarding the inheritance of land and/or buildings for children with dual citizenship in Indonesia, namely children who have foreigner status still have the right If you receive an inheritance, it will still not be the case that the property has ownership rights.